Phospholipogenic Pharmaceuticals Are Associated with a Higher Incidence of Histological Findings than Nonphospholipogenic Pharmaceuticals in Preclinical Toxicology Studies - Linda R. Barone; Scott Boyer; James R. Damewood; James Fikes; Paul J. Ciaccio (Journal of Toxicology)
While phospholipidosis is thought to be an adaptive response to chemical challenge, many phospholipogenic compounds are known to display adverse effects in preclinical species and humans. To investigate the link between phospholipogenic administration and incidence of preclinical histological signals, an internal AstraZeneca in vivo toxicology report database was searched to identify phospholipogenic and nonphospholipogenic compounds. The datasets assembled comprised 46 phospholipogenic and 62 nonphospholipogenic compounds. The phospholipogenic potential of these compounds was confirmed by a pathologist's interpretation and was supported by well-validated in silico and in vitro models. The phospholipogenic dataset contained 37 bases, 4 neutral compounds, 3 zwitterions, and 1 acid, whereas the nonphospholipogenic dataset contained 9 bases, 34 neutrals, 1 zwitterion, and 18 acids. Histologic findings were tracked for adrenal gland; bone marrow; kidney; liver; lung; lymph node; spleen; thymus; and reproductive organs. On average, plasma exposures were higher in animals dosed with the nonphospholipogenics. Phospholipogenics yielded proportionally more histologic changes (exclusive of phospholipidosis itself) in all organs. Statistically significant higher frequencies of liver necrosis, alveolitis/pneumonitis, as well as lymphocytolysis in the thymus, lymph nodes, and spleen occurred in response to phospholipogenics compared to that for nonphospholipogenics.